Blood Markers of Portal Hypertension Are Associated with Blood Loss and Transfusion Requirements during Orthotopic Liver Transplantation - Arshad, Freeha; Lisman, Ton; Porte, Robert J. (Seminars in Thrombosis and Hemostasis, 2020)
There is increasing evidence that portal hypertension plays a major role in bleeding risk during orthotopic liver transplantation (OLT). We investigated the association between preoperative blood levels of von Willebrand factor (VWF) and soluble CD163 (sCD163), which are established markers of portal hypertension, and blood loss and transfusion requirements during OLT. We measured levels of VWF and sCD163 in preoperative serum samples of 168 adult patients undergoing a primary OLT between 1998 and 2012. Preoperative levels of VWF and sCD163 correlated with the model of end-stage liver disease (MELD) score (r = 0.414, p < 0.001 and r = 0.382, p < 0.001, respectively). Patients with high VWF or sCD163 levels (VWF and sCD163 levels above the median) had a substantially increased risk of needing red blood cell transfusion compared with patients with low VWF or sCD163 levels (VWF and sCD163 levels below the median) (odds ratio 3.5 [95% confidence interval, CI 1.7–7.0] and 2.3 [95% CI 1.1–4.5], respectively). Blood loss was highest in patients with both high VWF or sCD163 levels and a high preoperative international normalized ratio. Elevated blood levels of markers of portal hypertension are associated with increased blood loss and transfusion requirements during OLT and support the notion that portal hypertension is an important contributor to perioperative blood loss.
Keywords: cirrhosis; red blood cell; von Willebrand factor; CD163; bleeding